The Impact of Online Media on Religious Authority - Mónika Andok (Religions)
The aim of this study is to reveal in an interpretive way how computer-mediated communication, the Internet, and social media can be grasped by authority models and how these new types of authority influence religious communities that are (also) present on online platforms. In some cases, computer-mediated communication weakened and made traditional church authorities porous, but in other cases, it specifically helped and strengthened them. In other words, the impact of digital media is not uniform or unidirectional in this respect. Although there is no doubt that the Internet has multiplied it, made it optional, and personalized it from the user’s point of view, it has made religious authority customizable. The power of choice means that, in the digital sphere, the user decides when, what form of network authority they will submit to, for how long, and why they do so. In the classics of the sociology of religion, the concept of authority appears in a hierarchical representation under the concepts of (social) order and rationality. In other words, it cannot be thought of in a way that is contrary to rationality and contrary to social order. In network communication, the concept of authority is subordinated to technology, or as Castells puts it, power can only be interpreted with the logic of the network. Of course, the technological network and its contents are under external (legal) control, but it is precisely the power of the symbolic struggles taking place here that shows how important this issue is in the 21st century. The concept of authority classified under technology will no longer be linked to order or rationality, but to the processes of control, datafication, and attention management on the part of the owners of the platforms, while from the users’ side to concepts such as identity, authenticity, choice, and voluntariness. Its boundaries will be malleable, and the phenomenon itself will multiply. In summary, we cannot talk about one single online religious authority but more types of religious authorities, which are continuously and discursively formed, change, and occasionally hybridize.